2002
DOI: 10.1210/mend.16.3.0784
|View full text |Cite
|
Sign up to set email alerts
|

Neogenesis of β-Cells in Adult BETA2/NeuroD-Deficient Mice

Abstract: BETA2/NeuroD, a basic helix-loop-helix transcription factor, is expressed in pancreatic endocrine cells during development and regulates insulin gene expression. We demonstrated previously that the endocrine pancreas of BETA2/NeuroD-deficient mice undergoes massive apoptosis and, consequently, animals die of diabetes shortly after birth. Here we show that a significant fraction of BETA2-deficient mice in a new genetic background can survive diabetes and live to adulthood through the process of beta-cell neogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…This finding is analogous to neuroD, which is essential for beta cell formation in pancreas and also for transcriptional regulation of insulin in the developed pancreas (52,53).…”
Section: Molecules That Form Emotional Memory Are Decreased In Neurod2-mentioning
confidence: 56%
“…This finding is analogous to neuroD, which is essential for beta cell formation in pancreas and also for transcriptional regulation of insulin in the developed pancreas (52,53).…”
Section: Molecules That Form Emotional Memory Are Decreased In Neurod2-mentioning
confidence: 56%
“…Indeed MafB, cMaf as well as NeuroD1/Beta2 are all involved in ␣ cell development and differentiation (17,18,20). Functionally, MafB-or cMaf-deficient mice show an important reduction in both insulin-and glucagon-positive cells throughout development indicating a significant role of MafB and cMaf in differentiation, replication, and/or survival of endocrine precursor cells (17,20).…”
Section: Discussionmentioning
confidence: 99%
“…NeuroD1 is a basic helix-loop-helix transcription factor that is essential for pancreatic and neuronal embryonic development and postnatal functions (13)(14)(15)(16)(17)(18). In the developing pancreas, NeuroD1 is detected as early as e9.5 in the early glucagon-producing populations (14).…”
mentioning
confidence: 99%
“…At this time the null mice display reduced insulin production and significantly decreased ␤ cell mass due to apoptosis (14). Interestingly, on certain genetic backgrounds, NeuroD1 null mice can survive postnatally with only mild hyperglycemia (13). These findings suggest that NeuroD1 plays a predominant role in the maintenance of functional ␤ cells after they have formed, although it has been suggested that the absence of an earlier phenotype may be due to redundancy with other NeuroD family members (20).…”
mentioning
confidence: 99%